Rangeland potential, quality and restoration strategies in North-Eastern Ethiopia : a case study conducted in the Southern Afar region - Gebremeskel, Kidane (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Agronomy))--University of Stellenbosch, 2006.